2017
DOI: 10.1371/journal.pone.0174518
|View full text |Cite
|
Sign up to set email alerts
|

Propionibacterium acnes biofilm is present in intervertebral discs of patients undergoing microdiscectomy

Abstract: BackgroundIn previous studies, Propionibacterium acnes was cultured from intervertebral disc tissue of ~25% of patients undergoing microdiscectomy, suggesting a possible link between chronic bacterial infection and disc degeneration. However, given the prominence of P. acnes as a skin commensal, such analyses often struggled to exclude the alternate possibility that these organisms represent perioperative microbiologic contamination. This investigation seeks to validate P. acnes prevalence in resected disc cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
108
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(118 citation statements)
references
References 39 publications
(41 reference statements)
5
108
0
Order By: Relevance
“…Microscopy revealed inflammatory cells spread throughout the tissue and in close proximity to the aggregates. Morphology of bacterial aggregates resembled those observed in a previous study of infected ligament reconstructions , but differed from those previously observed in LDH tissue . We hypothesize that the presence of an EPS matrix may obscure the morphology of individual cells as other studies also demonstrate difficulty in resolving single bacterial cells from FISH staining in several types chronic infections .…”
Section: Discussionsupporting
confidence: 48%
“…Microscopy revealed inflammatory cells spread throughout the tissue and in close proximity to the aggregates. Morphology of bacterial aggregates resembled those observed in a previous study of infected ligament reconstructions , but differed from those previously observed in LDH tissue . We hypothesize that the presence of an EPS matrix may obscure the morphology of individual cells as other studies also demonstrate difficulty in resolving single bacterial cells from FISH staining in several types chronic infections .…”
Section: Discussionsupporting
confidence: 48%
“…Although the culture result is controversial, many other methods like HE and modified Brown-Brenn staining [7], confocal scanning laser microscopy [14], fluorescence in situ hybridization [35], liquid chromatography-tandem mass spectrometry (LC-MS/MS) [36] and PCR assay [12,15,36,37] have provided the evidence for the presence of bacteria. Studies have also demonstrated the differences between genotypes of P. acnes from intervertebral discs and skin.…”
Section: Discussionmentioning
confidence: 99%
“…Every study reported more than one kind of bacteria except the studies by Javanshir [13] and Lin [9] (See supplementary Table 2). Two studies included more than 300 cases [3,14]. One study [15] had more than 200 cases, and four studies reported more than 100 cases [9,13,16,17].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Nonetheless, if an attempt is to be made to investigate the prevalence of low virulence infection, such as P. acnes, with cervical discs, then we feel the methodological and data analysis issues described here may have compromised any clear conclusions, especially as P. acnes does appear to be significantly represented within infected discs [2].…”
mentioning
confidence: 91%
“…To ensure that the 95% confidence interval estimate of the proportion positive cases is within 5% of the true proportion, a sample size of approximately 350 cases is necessary. Indeed, in our previous work we looked at 368 patients to draw statistically relevant conclusions [2]. 3.…”
mentioning
confidence: 99%